High-performance X-ray excited rare earth afterglow material, preparation method and application of high-performance X-ray excited rare earth afterglow material in imaging field

By adopting a three-layer rare earth afterglow material, doping Bi3+ and Ba2+ ions, forming lattice mismatch and defect energy levels, the problems of insufficient afterglow performance and high irradiation dose in the prior art are solved, and efficient X-ray imaging is achieved.

CN119776006AActive Publication Date: 2025-04-08CHINA JILIANG UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510255372.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-04-08
Estimated Expiration
2045-03-05

AI Technical Summary

Technical Problem

The afterglow performance of existing X-ray excitation rare earth afterglow materials is insufficient, which cannot meet the requirements of actual application, and the radiation dose is high, which affects safety.

Method used

The rare earth afterglow material with a three-layer structure is NaLu0.3Y0.7F4, respectively. The intermediate layer is doped with Bi3+ and Ba2+ ions, forming lattice mismatch and defect energy levels, and improving X-ray absorption and secondary electron capture efficiency.

Benefits of technology

It significantly improves the afterglow luminescence intensity and duration, reduces the X-ray irradiation dose, and is suitable for high-resolution, low-dose X-ray imaging field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776006A_ABST
    Figure CN119776006A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rare earth afterglow materials, and discloses a high-performance X-ray excited rare earth afterglow material, a preparation method and application of the high-performance X-ray excited rare earth afterglow material in the imaging field, and the chemical composition general formula of the high-performance X-ray excited rare earth afterglow material is NaLuzY < 0.7 > F < 4 > at-NaLu0. 8BixF < 4 >: BaY / Dym at-NaLuzY < 0.7 > F < 4 >. The high-performance X-ray excited rare earth afterglow material comprises a three-layer structure including an inner core, a middle layer and a shell layer, and the inner core, the shell layer and the middle layer have different matrix components, so that lattice mismatch is formed at the interface of the shell layer. Strong afterglow luminescence can be generated after X-ray irradiation, the afterglow performance is high, the afterglow lasting time is long, and the X-ray fluorescent powder can be applied to the field of X-ray imaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rare earth afterglow materials, and in particular to a high-performance X-ray excited rare earth afterglow material, a preparation method and application thereof in the field of imaging. Background Art

[0002] X-ray imaging technology based on traditional block scintillators is difficult to obtain the three-dimensional structure inside an object. It usually requires high X-ray radiation doses or complex instruments and equipment to obtain three-dimensional information through image reconstruction. Compared with traditional block scintillators, the development of new flexible X-ray detectors is easier to achieve three-dimensional imaging, and X-ray excited afterglow materials are a good choice. Studies have shown that rare earth ion-doped fluorides have afterglow properties excited by X-rays and can be used to make flexible films to achieve three-dimensional imaging. However, the afterglow performance requires a high radiation dose to achieve, which cannot meet the requirements of practical applications. It is urgent to explore effective methods to significantly improve the afterglow performance, thereby effectively reducing the irradiation dose and ensuring safety during use.

[0003] There are also some studies and applications related to X-ray excited rare earth afterglow materials in the prior art.

[0004] (1) For example, the invention patent application with application number 202011538445.7, entitled "Near-infrared second-region luminescent long afterglow nanoprobe based on X-ray excitation, preparation method and its application in in vivo imaging analysis", combines rare earth fluoride nanocrystals with small phonon energy and high luminescence efficiency with X-rays, and regulates the doping of rare earth ions to achieve the construction of near-infrared second-region long afterglow luminescent nanoprobe, and is used for deep in vivo tissue imaging. However, the afterglow nanoprobe of this application is a core-shell two-layer structure, and its preparation method is also for the preparation of the afterglow nanoprobe, and the duration of the afterglow also needs to be improved.

[0005] (2) Another example is the invention patent application with application number 202311466202.0, entitled "An ultraviolet luminescent long afterglow material based on X-ray excitation and its application in high-confidential X-ray imaging encryption". Its rare earth long afterglow nanoparticles have pure ultraviolet luminescence that is imperceptible to the naked eye. The prepared flexible memory film can realize three-dimensional ray encryption of curved objects with high spatial resolution and good recyclability. The encrypted X-ray imaging can be safely stored in the film and optically decoded by a layer of perovskite nanocrystals. However, it is a single-layer structure and the duration of the afterglow needs to be improved.

[0006] (3) For example, the application number is 202410362486.7, and the name is an authorized invention patent for a rare earth element-doped pyrophosphate long afterglow material that can only be excited by X-rays, and its preparation method and application. This material can only be excited by X-rays and produces bright green, purple, reddish brown, and orange-red light visible to the naked eye, but cannot be excited by white light and ultraviolet light. Therefore, it will not be affected by natural light in daily life, and after being irradiated by X-rays for a period of time, it can still be re-excited with hot water to emit bright green light, and can be used for daily personal home X-ray dose detection.

[0007] (4) For example, the invention patent application with application number 202410696431.X and titled "An X-ray-excited borate long afterglow luminescent material and its preparation method" can be effectively excited by X-rays to produce long afterglow luminescence with high afterglow intensity and long duration. The borate long afterglow luminescent material prepared by the present invention can produce afterglow in the range of 300nm-400nm after being excited. The prepared borate long afterglow luminescent material can be mixed with organic polymer materials such as epoxy resin and curing agent to form a film or resin body as a luminescent film or a blue afterglow luminescent device. However, it mainly uses borates and is mainly used in luminescent devices, and the duration of afterglow still needs to be enhanced. Summary of the invention

[0008] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a high-performance X-ray excited rare earth afterglow material, a preparation method and its application in the imaging field, which can produce strong afterglow luminescence after X-ray irradiation, has strong afterglow performance and long afterglow duration, and can be used in the field of X-ray imaging technology, providing a new structural design idea for the development of high-performance rare earth afterglow materials.

[0009] The present invention is implemented by the following technical solution: a high-performance X-ray excited rare earth afterglow material, the chemical composition formula of which is: NaLu z Y 0.7 F 4 @NaLu 0.8 Bi x F 4 :Ba Y / Dy m @NaLu z Y 0.7 F 4 ,

[0010] Where x is the molar content of Bi, 0.18≤x≤0.25, Y is the molar content of Ba, 0.12≤Y≤0.25,

[0011] z is the molar content of Lu, 0.25≤z≤0.4, and m is the molar content of Dy, 0.035≤m≤0.05.

[0012] Preferably, x=0.2, Y=0.2, z=0.3, and m=0.04.

[0013] Preferably, the high-performance X-ray excited rare earth afterglow material comprises a three-layer structure of a core, an intermediate layer and an outer shell, wherein the core and the outer shell are both NaLu 0.3 Y 0.7 F 4 , the middle layer is NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 , the luminescence center is located in the middle layer, a large amount of Dy 3+ The ions are located at the interface; the core, shell and middle layers have different matrix components, which forms a lattice mismatch at the shell interface and reduces the F - The binding energy of the ions increases the probability of the formation of Frankel defects at the interface.

[0014] Preferably, the intermediate layer of the high performance X-ray excited rare earth afterglow material is doped with Bi 3+ Ions increase the X-ray absorption coefficient without changing the crystal structure.

[0015] Preferably, the intermediate layer of the high performance X-ray excited rare earth afterglow material is doped with Ba 2+ ions, producing F in the lattice - Ion vacancies form defect energy levels, which improve the capture efficiency of secondary electrons and the energy transfer efficiency from secondary electrons to rare earth ions.

[0016] A method for preparing a high-performance X-ray excited rare earth afterglow material, used for preparing the above-mentioned high-performance X-ray excited rare earth afterglow material, comprises the following steps:

[0017] Step 1: First prepare NaLu 0.3 Y 0.7 F 4 Core nanocrystals;

[0018] Step 2: Then use the core nanocrystals in step 1 to prepare NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 : Ba / Dy core-shell nanocrystals;

[0019] Step 3: Then use the core-shell nanocrystals in step 2 to prepare NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi0.2 F 4 :Ba / Dy@NaLu 0.3 Y 0.7 F 4 Afterglow material.

[0020] Furthermore, the preparation steps of the core nanocrystals in step 1 specifically include:

[0021] Step 11: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0022] Step 12: After the solution is cooled naturally to room temperature, 4-6 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-90° C. for half an hour;

[0023] Step 13: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 80-100 minutes, and then naturally cooled to room temperature;

[0024] Step 14: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 Core nanocrystals were stored in 4-6 ml of cyclohexane.

[0025] Furthermore, the preparation steps of the core-shell nanocrystals in step 2 specifically include:

[0026] Step 21: adding 2 mmol of sodium acetate, 0.55-0.69 mmol of lutetium acetate, 0.2 mmol of bismuth acetate, 0.1-0.2 mmol of barium acetate, and 0.01-0.05 mmol of dysprosium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0027] Step 22: After the solution is naturally cooled to 70° C., the core nanocrystal solution obtained in step 14 is added to the reaction solution in step 21, and then kept at 80-100° C. for half an hour;

[0028] Step 23: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour;

[0029] Step 24: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature;

[0030] Step 25: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 : Ba / Dy core-shell nanocrystals, stored in 4-6 ml cyclohexane.

[0031] Furthermore, the preparation steps of the rare earth afterglow material in step 3 specifically include:

[0032] Step 31: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0033] Step 32: After the solution is naturally cooled to 70° C., the core-shell nanocrystal solution obtained in step 25 is added to the reaction solution of step 31, and then kept at 80-100° C. for half an hour;

[0034] Step 33: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour;

[0035] Step 34: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310° C., and kept at this temperature for 100-120 minutes, and then naturally cooled to room temperature;

[0036] Step 35: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba / Dy@NaLu 0.3 Y 0.7 F 4 Afterglow material.

[0037] A high-performance X-ray excited rare earth afterglow material, which can be used in the field of imaging.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. A high-performance X-ray excited rare earth afterglow material of the present invention comprises a three-layer structure of a core, an intermediate layer and an outer shell layer, wherein the luminescent center is located in the intermediate layer, and Bi is doped in the intermediate layer. 3+ ions, which can increase the X-ray absorption coefficient without changing the crystal structure; the middle layer is doped with Ba 2+ Ion, Ba 2+ Ion substitution Lu 3+ The ions occupy the lattice points. In order to maintain the charge balance of the system, F - Ion vacancies form defective energy levels, which improve the efficiency of secondary electron capture and the energy transfer efficiency from secondary electrons to rare earth ions; the core and shell layers are NaLu 0.3 Y 0.7 F 4 , so that the lattice mismatch is formed at the shell interface, reducing the F - The binding energy of the ions increases the probability of the formation of Frankel defects at the interface under X-ray excitation.

[0040] 2. The high-performance X-ray excited rare earth afterglow material of the present invention forms a large number of defect states at the interface when the product is irradiated by X-rays, which can store a large number of secondary electrons. After the irradiation stops, these electrons are released to fill the excited state energy levels of the rare earth ions, thereby generating very strong afterglow luminescence, strong afterglow performance, and long afterglow duration.

[0041] 3. The high-performance X-ray excited rare earth afterglow material of the present invention can be applied to the field of high-resolution, low-dose X-ray imaging technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 X-ray diffraction pattern of

[0043] Figure 2 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y0.7 F 4 Transmission electron micrograph of

[0044] Figure 3 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Afterglow spectrum after X-ray excitation stops;

[0045] Figure 4 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Afterglow spectrum after 5 days;

[0046] Figure 5 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 The afterglow intensity and Bi 3+ The relationship curve of ion concentration;

[0047] Figure 6 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 The afterglow intensity of Ba 2+ The relationship curve of ion concentration;

[0048] Figure 7 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 The afterglow intensity of Dy 3+ The relationship curve of ion concentration;

[0049] Figure 8 :NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 The afterglow intensity is related to the Lu in the outer shell 3+ The relationship curve of ion concentration;

[0050] Fig. 9 :NaLu under X-ray excitation 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 With NaLuF 4 : Dy afterglow intensity comparison;

[0051] Fig.10 : NaLu in Example 4 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Imaging effect of afterglow luminescence. DETAILED DESCRIPTION

[0052] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict.

[0053] Example 1

[0054] A high-performance X-ray excited rare earth afterglow material, the general chemical composition formula is:

[0055] NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 ,

[0056] The preparation method comprises the following steps in sequence:

[0057] Step 1: Preparation of NaLu 0.3 Y 0.7 F 4 Core nanocrystal; which specifically comprises the following steps:

[0058] Step 11: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0059] Step 12: After the solution is cooled naturally to room temperature, 4-6 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-90° C. for half an hour;

[0060] Step 13: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 80-100 minutes, and then naturally cooled to room temperature;

[0061] Step 14: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 Core nanocrystals were stored in 4-6 ml of cyclohexane.

[0062] Step 2: Prepare NaLu using the core nanocrystals from step 1 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 : Ba / Dy core-shell nanocrystals; which specifically comprises the following steps:

[0063] Step 21: adding 2 mmol of sodium acetate, 0.55-0.69 mmol of lutetium acetate, 0.2 mmol of bismuth acetate, 0.1-0.2 mmol of barium acetate, and 0.01-0.05 mmol of dysprosium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0064] Step 22: After the solution is naturally cooled to 70° C., the core nanocrystal solution obtained in step 14 is added to the reaction solution in step 21, and then kept at 80-100° C. for half an hour;

[0065] Step 23: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour;

[0066] Step 24: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature;

[0067] Step 25: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 : Ba / Dy core-shell nanocrystals, stored in 4-6 ml cyclohexane.

[0068] Step 3: Prepare NaLu using the core-shell nanocrystals in step 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba / Dy@NaLu 0.3 Y 0.7 F 4 Afterglow material, which specifically includes the following steps:

[0069] Step 31: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution;

[0070] Step 32: After the solution is naturally cooled to 70° C., the core-shell nanocrystal solution obtained in step 25 is added to the reaction solution of step 31, and then kept at 80-100° C. for half an hour;

[0071] Step 33: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour;

[0072] Step 34: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310° C., and kept at this temperature for 100-120 minutes, and then naturally cooled to room temperature;

[0073] Step 35: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba / Dy@NaLu 0.3 Y 0.7 F 4 Afterglow material.

[0074] Example 2

[0075] A high-performance X-ray excited rare earth afterglow material, the general chemical composition formula is:

[0076] NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 ,

[0077] The preparation method comprises the following steps in sequence:

[0078] (1) Add 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate, and 0.7 mmol of yttrium acetate to a mixture of 7 ml of oleic acid and 10 ml of octadecene. oC for 1 hour to obtain an anhydrous transparent solution;

[0079] (2) After the solution was cooled to room temperature, 4 ml of methanol solution containing 4 mmol of ammonium fluoride was added, and then o C keep warm for half an hour;

[0080] (3) After the methanol solution has completely evaporated, quickly raise the temperature to 300 o C, and keep at this temperature for 80 minutes, and then cool naturally to room temperature;

[0081] (4) Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 Core nanocrystals, stored in 4 mL of cyclohexane;

[0082] (5) 2 mmol of sodium acetate, 0.61 mmol of lutetium acetate, 0.2 mmol of bismuth acetate, 0.15 mmol of barium acetate, and 0.04 mmol of dysprosium acetate were added to a mixture of 6 ml of oleic acid and 8 ml of octadecene. The mixture was stirred at 160 °C under nitrogen atmosphere. o C for 1 hour to obtain an anhydrous transparent solution;

[0083] (6) Wait for the solution to cool naturally to 70 o C, the core nanocrystal solution obtained in step (4) is added to the reaction solution in step (5), and then heated at 90 o C keep warm for half an hour;

[0084] (7) After the solution was cooled to room temperature, 8 ml of methanol solution containing 4 mmol of ammonium fluoride was added and then heated at 60 o C keep warm for half an hour;

[0085] (8) After the methanol solution has completely evaporated, quickly raise the temperature to 310 o C, and keep at this temperature for 100 minutes, and then cool naturally to room temperature;

[0086] (9) The obtained nanocrystals are washed with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 Core-shell nanocrystals, stored in 4 mL of cyclohexane;

[0087] (10) 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate, and 0.7 mmol of yttrium acetate were added to a mixture of 6 ml of oleic acid and 8 ml of octadecene. The mixture was stirred at 160 °C under nitrogen atmosphere. o C for 1 hour to obtain an anhydrous transparent solution;

[0088] (11) Wait until the solution cools naturally to 70 o C, the core-shell nanocrystal solution obtained in step (9) is added to the reaction solution in step (10), and then heated at 80 o C keep warm for half an hour;

[0089] (12) After the solution was cooled to room temperature, 12 ml of methanol solution containing 4 mmol of ammonium fluoride was added and then heated at 60 o C keep warm for half an hour;

[0090] (13) After the methanol solution has completely evaporated, quickly raise the temperature to 290 o C, and keep at this temperature for 120 minutes, and then cool naturally to room temperature;

[0091] (14) The obtained nanocrystals are washed with a mixture of ethanol and cyclohexane and dried to obtain NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Afterglow material.

[0092] Refer to the attached Figure 1 As shown, NaLu prepared by the above method 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Afterglow material, powder X-ray diffraction analysis showed that the product was a pure hexagonal phase.

[0093] Refer to the attached Figure 2 As shown, transmission electron microscopy analysis showed that the average crystallite size of the product was 80 nanometers.

[0094] After 5 minutes of X-ray irradiation, the X-ray source was turned off and the product showed Dy3+ The characteristic transition lines of Figure 3 shown.

[0095] After 5 days, the product irradiated by X-rays still has a strong emission spectrum, indicating that the afterglow time of the product is greater than 5 days. Figure 4 shown.

[0096] To prove that 3+ Ions can enhance the afterglow luminescence performance by improving X-ray absorption. In this example, different Bi 3+ Afterglow performance of ion concentration samples. Figure 5 As shown, with Bi 3+ The ion concentration gradually increased from 0.1 (10% by mole) to 0.2, and the afterglow luminescence intensity was significantly improved, indicating that Bi doping 3+ Ions can improve afterglow performance, but Bi 3+ When the ion doping concentration is too high, the coordination environment of the rare earth ions changes, causing the afterglow performance to weaken. 3+ When the ion concentration is 0.2, the afterglow performance is the strongest.

[0097] To prove that Ba 2+ The influence of ion doping on afterglow performance is compared in this embodiment. 2+ Afterglow performance of ion concentration samples. Figure 6 As shown, no Ba 2+ The afterglow intensity of the system doped with Ba is much lower than that of the system doped with Ba 2+ Ion-doped system; with Ba 2+ When the ion concentration is gradually increased to 0.15 (15% by mole), the afterglow luminescence intensity is significantly improved. This is because Ba is doped in the middle layer. 2+ Ion, Ba 2+ Ion substitution Lu 3+ The ions occupy the positions of the lattice points. In order to maintain the charge balance of the system, F - Ion vacancies form defect energy levels, which can participate in capturing secondary electrons and increase the electron storage density of defect states. At the same time, these energy levels can improve the energy transfer efficiency from secondary electrons to the excited state energy levels of rare earth ions, thereby greatly improving the afterglow performance. 2+ The ion doping concentration leads to excessive defects in the lattice, which increase the probability of non-radiative relaxation of rare earth ions and thus reduce the afterglow luminescence.

[0098] Rare earth ions have a rich energy level structure, and non-radiative cross relaxation processes are easily generated between activated ions. In order to further optimize the afterglow performance, the concentration of activated ions is adjusted in this embodiment. Figure 7 As shown, Dy 3+ The optimum doping concentration is 0.04 (4% molar concentration).

[0099] In order to prove the particularity of the shell structure, this example compares the Lu 3+ The influence of ion concentration on afterglow performance. Figure 8 As shown, with the Lu in the outer shell 3+ As the ion concentration gradually increased from 0.1 to 0.3, the afterglow intensity was significantly improved, indicating that NaLu 0.3 Y 0.7 F 4 The shell layer can not only passivate the surface of the nanocrystal and reduce the energy transfer efficiency from activated ions to surface defects, but also tailor the interface phonon state density, further reducing the probability of non-radiative relaxation of rare earth ions, thereby improving the afterglow performance.

[0100] Example 3

[0101] In order to verify and compare the NaLu in Example 2 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 Afterglow material has strong afterglow performance, designed NaLuF 4 : Dy system is used as comparative example 1.

[0102] Comparative Example 1

[0103] FWf 4 :The preparation process of Dy includes the following steps:

[0104] (1) Add 2 mmol of sodium acetate, 0.96 mmol of lutetium acetate, and 0.04 mmol of dysprosium acetate to a mixture of 7 ml of oleic acid and 10 ml of octadecene. o C for 1 hour to obtain an anhydrous transparent solution;

[0105] (2) After the solution was cooled to room temperature, 4 ml of methanol solution containing 4 mmol of ammonium fluoride was added, and then o C keep warm for half an hour;

[0106] (3) After the methanol solution has completely evaporated, quickly raise the temperature to 300 o C, and keep at this temperature for 80 minutes, and then cool naturally to room temperature;

[0107] (4) The obtained nanocrystals are washed with a mixture of ethanol and cyclohexane to obtain NaLuF 4 :Dy system.

[0108] Refer to the attached Fig. 9 As shown, under the same irradiation and test conditions, NaLu 0.3 Y 0.7 F 4 @NaLu 0.8 Bi 0.2 F 4 :Ba 0.2 / Dy 0.04 @NaLu 0.3 Y 0.7 F 4 The afterglow intensity is the NaLuF in Example 1 4 : 53 times that of Dy system.

[0109] Example 4

[0110] In order to further verify that the system designed in the present invention has good application prospects in the field of imaging, an imaging experiment was carried out in this example.

[0111] An application of a high-performance X-ray excited rare earth afterglow material in the field of imaging, using the high-performance X-ray excited rare earth afterglow material prepared by the present invention to prepare a scintillation film, the process of which includes:

[0112] (1) First, the dried sample and the pre-prepared PMMA toluene solution were mixed and stirred, wherein the ratio of sample powder to PMMA powder was 2:3;

[0113] (2) Stir thoroughly with a magnetic stirrer until the solution is clear and transparent, then use a pipette to slowly drip the solution into the glass mold. Avoid the generation of bubbles during the dripping process.

[0114] (3) After toluene evaporates naturally for 12 hours, a uniform and transparent scintillator film is prepared.

[0115] Refer to the attached Fig.10 As shown, a common screw is placed in a capsule, and the afterglow material prepared by the present invention is a scintillation film, which is wrapped on the surface of the capsule. After irradiation with X-rays for 5 minutes, the film is removed, and the image obtained by the camera can clearly see the screw inside the capsule and its gear-like structure, which can have good application prospects in the field of imaging.

[0116] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A high-performance X-ray excited rare earth afterglow material, characterized in that: The general chemical formula is: NaLu z Y 0.7 F4@NaLu 0.8 Bi x F4: Ba Y / Dy m @NaLu z Y 0.7 F 4; Where x is the molar content of Bi, 0.18≤x≤0.25, Y is the molar content of Ba, 0.12≤Y≤0.25, z is the molar content of Lu, 0.25≤z≤0.4, m is the molar content of Dy, 0.035≤m≤0.

05.

2. The high performance X-ray excited rare earth afterglow material according to claim 1, characterized in that: Said x=0.2, y=0.2, z=0.3, m=0.

04.

3. The high performance X-ray excited rare earth afterglow material according to claim 2, characterized in that: It consists of three layers: inner core, middle layer and outer shell. Both the inner core and outer shell are NaLu 0.3 Y 0.7 F4, middle layer is NaLu 0.8 Bi 0.2 F4: Ba 0.2 / Dy 0.04 , the luminescence center is located in the middle layer, a large amount of Dy 3+ The ions are located at the interface; The core, shell and middle layers have different matrix components, which form a lattice mismatch at the shell interface and reduce the F - The binding energy of the ions increases the probability of the formation of Frankel defects at the interface.

4. The high performance X-ray excited rare earth afterglow material according to claim 3, characterized in that: Bi doped in the middle layer 3+ Ions increase the X-ray absorption coefficient without changing the crystal structure.

5. The high performance X-ray excited rare earth afterglow material according to claim 4, characterized in that: Ba doped intermediate layer 2+ ions, producing F in the lattice - Ion vacancies form defect energy levels, which improve the capture efficiency of secondary electrons and the energy transfer efficiency from secondary electrons to rare earth ions.

6. The method for preparing a high-performance X-ray excited rare earth afterglow material according to any one of claims 2 to 5, characterized in that: The steps include: Step 1: Preparation of NaLu 0.3 Y 0.7 F4 core nanocrystals; Step 2: Prepare NaLu using the core nanocrystals from step 1 0.3 Y 0.7 F4@NaLu 0.8 Bi 0.2 F4: Ba / Dy core-shell nanocrystals; Step 3: Prepare NaLu using the core-shell nanocrystals in step 2 0.3 Y 0.7 F4@NaLu 0.8 Bi 0.2 F4: Ba / Dy@NaLu 0.3 Y 0.7 F4 afterglow material.

7. The method for preparing the high performance X-ray excited rare earth afterglow material according to claim 6, characterized in that: The steps for preparing core nanocrystals include: Step 11: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution; Step 12: After the solution is cooled naturally to room temperature, 4-6 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-90° C. for half an hour; Step 13: After the methanol solution is completely volatilized, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 80-100 minutes, and then naturally cooled to room temperature; Step 14: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F4 core nanocrystals were stored in 4-6 ml cyclohexane.

8. The method for preparing the high performance X-ray excited rare earth afterglow material according to claim 7, characterized in that: The preparation steps of core-shell nanocrystals include: Step 21: adding 2 mmol of sodium acetate, 0.55-0.69 mmol of lutetium acetate, 0.2 mmol of bismuth acetate, 0.1-0.2 mmol of barium acetate, and 0.01-0.05 mmol of dysprosium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-12 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution; Step 22: After the solution is naturally cooled to 70° C., the core nanocrystal solution obtained in step 14 is added to the reaction solution in step 21, and then kept at 80-100° C. for half an hour; Step 23: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour; Step 24: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310°C, and kept at this temperature for 90-130 minutes, and then naturally cooled to room temperature; Step 25: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane to obtain NaLu 0.3 Y 0.7 F4@NaLu 0.8 Bi 0.2 F4: Ba / Dy core-shell nanocrystals, stored in 4-6 ml cyclohexane.

9. The method for preparing the high performance X-ray excited rare earth afterglow material according to claim 8, characterized in that: The preparation steps of rare earth afterglow material include: Step 31: adding 2 mmol of sodium acetate, 0.3 mmol of lutetium acetate and 0.7 mmol of yttrium acetate according to molar percentage to a mixed solution containing 6-8 ml of oleic acid and 8-10 ml of octadecene, and keeping the mixture at 140-160° C. for 1 hour under the protection of nitrogen to obtain an anhydrous transparent solution; Step 32: After the solution is naturally cooled to 70° C., the core-shell nanocrystal solution obtained in step 25 is added to the reaction solution of step 31, and then kept at 80-100° C. for half an hour; Step 33: After the solution is cooled naturally to room temperature, 8-12 ml of a methanol solution containing 4 mmol of ammonium fluoride is added, and then the mixture is kept at 60-80° C. for half an hour; Step 34: After all the methanol solution has evaporated, the temperature is rapidly raised to 290-310° C., and kept at this temperature for 100-120 minutes, and then naturally cooled to room temperature; Step 35: Wash the obtained nanocrystals with a mixture of ethanol and cyclohexane, and dry them to obtain NaLu 0.3 Y 0.7 F4@NaLu 0.8 Bi 0.2 F4: Ba / Dy@NaLu 0.3 Y 0.7 F4 afterglow material.

10. Application of the high performance X-ray excited rare earth afterglow material prepared by the method of claim 9 in the field of imaging.

Citation Information

Patent Citations

  • Single-spectrum red-light nanocrystalline material and preparation method thereof

    CN107541204A

  • Rare earth doped fluoride long afterglow particle as well as preparation method and application thereof

    CN111876154A

  • Near-infrared two-zone light-emitting long afterglow nanoprobe based on X-ray excitation, preparation method and application of nanoprobe in living body imaging analysis

    CN112480925A

  • Wavelength-adjustable near-infrared second window long afterglow nanoprobe and synthesis method thereof

    CN113234444A

  • High-quantum-efficiency green light up-conversion core-shell nanocrystal and preparation method thereof

    CN114163992A